A physiological overview of the demands, characteristics, and adaptations of highly trained artistic swimmers: a literature review - Viana, E.; Bentley, D. J.; Logan-Sprenger, H. M. (Sports Medicine, 2019)
Artistic swimming (AS) is a very unique sport consisting of difficult artistically choreographed routines ranging in the number of athletes (one to ten: solo, duet, team, combination, highlight routine) and with elements performed quickly and precisely above, below, and on the surface of the water. As a result, the physical and physiological demands placed on an athlete are unique to the sport with the most pronounced adaptation being the bradycardic response to long apneic periods spent underwater while performing strenuous movements. This indeed influences training prescription and the desired training outcomes. This review paper explores the physiological demands of AS, the physiological characteristics that influence AS performance, and innovative approaches to enhancing training and performance in elite performers.